2002
DOI: 10.4049/jimmunol.169.7.3581
|View full text |Cite
|
Sign up to set email alerts
|

B7-H1 Is Expressed by Human Endothelial Cells and Suppresses T Cell Cytokine Synthesis

Abstract: Human endothelial cells (ECs) provide costimulatory signals sufficient to activate resting memory T cells to produce IL-2 and IFN-γ, at least in part through CD58-CD2 interactions. Recently, the B7-like molecule, B7-H1 (PD-L1), was described and shown to regulate T cell activation; however, there are conflicting reports on whether it stimulates or inhibits T cell cytokine synthesis. B7-H1 is not expressed constitutively by ECs; however, it is rapidly induced by IFN-γ, and synergistically by IFN-γ and TNF. In i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
192
3
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(207 citation statements)
references
References 43 publications
11
192
3
1
Order By: Relevance
“…The expression of PD-L1 on VECs has been related to the negative regulation of T cells. 17,18 In this study, we demonstrate that VECs not only express PD-L1, but also B7-1 (CD80), one of its receptors. The interaction between PD-1 and PD-L1 is well established as playing a vital role in controlling T-cell responses in a variety of contexts, from development to autoimmunity to microbial pathogenesis to tumor immunity.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The expression of PD-L1 on VECs has been related to the negative regulation of T cells. 17,18 In this study, we demonstrate that VECs not only express PD-L1, but also B7-1 (CD80), one of its receptors. The interaction between PD-1 and PD-L1 is well established as playing a vital role in controlling T-cell responses in a variety of contexts, from development to autoimmunity to microbial pathogenesis to tumor immunity.…”
Section: Discussionmentioning
confidence: 53%
“…15,16 Interestingly, PD-L1 also has been reported to be present on VECs under basal conditions, and the surface expression of PD-L1 on VECs can be increased by interferon-␣, -␤, and -␥. 17,18 However, the anti-angiogenic effect of PD-L1 has not been demonstrated to date. Here, we provide evidence for a novel regulatory function for PD-L1 in VEC proliferation in vitro and corneal angiogenesis in vivo.…”
mentioning
confidence: 99%
“…In addition, B7-H1 was inducible in epidermal KC. Recent reports have suggested a regulatory function for B7-H1 expressed on normal tissue cells, such as endothelial cells [35] and trophoblasts [36,37]. Thus, it is possible that KC expressing B7-H1 may provide a regulatory function similar to that of APC at the local site.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of B7-H1 molecule in the current primary cell lines is not dependent on inflammatory cytokines (g-IFN and TNF-a) known to induce B7-H1. [37][38][39] The similarity in the expression of B7-H1 in fibroblasts and epithelial cell cultures, obtained form either normal or tumor tissues, suggests that B7-H1 is directly related to proliferation and not tumorgenesis (cell transformation). Similarly, Parsa et al have recently found that expression of B7-H1 in human astrocytes was dependent on Akt activation but not on cellular immortalization or transformation.…”
Section: Discussionmentioning
confidence: 99%